Analyzing the Relationship between Moral Climate and Sense of Belonging to School and Academic Success: The Mediating Role of Iraqi Students\' Academic Hardiness - Ne'ma Zakari Rashid Aziz; Behnaz Mohajeran (International Journal of Ethics and Society)
Introduction: Most learning happens through formal education in schools, and effective school systems require a correct combination of educational resources and facilities, the moral orientation of the school atmosphere, and the characteristics of students. Therefore, the current research was conducted with the aim of analyzing the relationship between ethical climate and the sense of belonging to school and academic success with regard to the mediating role of students' academic hardiness. Material and Methods: The present research method was descriptive-correlation. The statistical population consisted of 527 students of the fifth grade of literature in Karbala city (Iraq), 334 of them were selected using the Cochran formula by random cluster sampling. To collect data, four standard questionnaires were used: ethical climate, school belongingness skills, academic hardiness and academic success. Data analysis was done using Pearson's correlation coefficient analysis and path analysis in SPSS and Lisrel statistical software. Results: The results showed that the moral components have a direct and positive relationship with the sense of belonging to the school. The results also showed that ethical climate has a positive and significant relationship with academic success. Also, the mediating role of academic hardiness has a positive and significant effect on the relationship between ethical climate and the sense of belonging to the school and the academic success of students. Conclusion: According to the findings of this research, any improvement in the ethical climate of the school can be associated with the improvement of the sense of belonging in the school and academic progress.